«Student Voice» per la valorizzazione delle risorse personali - Alessandro Di Vita (LED Edizioni Universitarie, 2017)
«Student Voice» to increase the value of personal resources. A new pedagogical movement has spread to Italy over the last ten years to inspire «education policy makers» and teachers at all levels of education to listen carefully to the voices as well as the needs and interests of all the students. This is the «Student Voice» movement, born in the nineties in the UK and spread to some english-speaking countries (USA, Canada, Australia). This movement supports the active and responsible participation of all students in the training processes that take place in schools and universities: specifically, this participation occurs in the classroom teaching, their professors' researches and decision-making processes with which the educational policies related to the rights and interests of students are implemented. In this article, after presenting the theoretical backgrounds that the english-speaking pioneers of the «Student Voice» perspective have identified and the way in which Italian researchers have transposed their suggestions, we describe the most significant ways that those Italian researchers who are participating in this emerging perspective have experimented to enhance the voice of students and improve their participation in school and university life. We will try to capture the potentials and limits of the «Stude nt Voice» movement.